Friends, foes, and future directions : U.S. partnerships in a turbulent world - Binnendijk, Hans (Strategic rethink., 2016)
" ... RAND experts explore the elements of a national strategy for the conduct of U.S. foreign and security policy in this administration and the next. The report evaluates three broad strategies for dealing with U.S. partners and adversaries in Europe, Asia, and the Middle East in a time of diminishing defense budgets and an American public preference for a domestic focus. The three strategies are to be more assertive, to be more collaborative, or to retrench from international commitments. All three of these alternative approaches are constrained and a balance will need to be struck among them -- that balance may differ from region to region."--Publisher's description